Towards the Use of a Tree Branching Logic in the Environment of a Hospital Information System - Berney, J.-Ph.; Baud, R.; Scherrer, J.-R. (Methods of Information in Medicine, 1980)
It is well known that Frame Selection Systems (FFS) have proved both popular and effective in physician-machine and patient-machine dialogue. A formal algorithm for definition of a Frame Selection System for handling man-machine dialogue is presented here. Besides, it is shown how the natural medical language can be handled using the approach of a tree branching logic. This logic appears to be based upon ordered series of selections which enclose a syntactic structure. The external specifications are discussed with regard to convenience and efficiency. Knowing that all communication between the user and the application programmes is handled only by FSS software, FSS contributes to achieving modularity and, therefore, also maintainability in a transaction-oriented system with a large data base and concurrent accesses.
Keywords: Tree Branching Logic; Medical Linguistics; Hospital Information Systems; Clinical Data